#y=Pe^(ax) + Qe^(bx)# Show that #(d^2y)/dx^2-(a+b)dy/dx+aby=0#?

Answer 1

See below

Let #y=Pe^(ax)+Qe^(bx)#

Then

#aby=ab(Pe^(ax)+Qe^(bx))=abPe^(ax) + abQe^(bx)#
And # dy/dx=aPe^(ax)+bQe^(bx)#
#rArr (a+b)dy/dx = (a+b)(aPe^(ax)+bQe^(bx))= a^2Pe^(ax)+abQe^(bx)+abPe^(ax)+b^2Qe^(bx)#
And #(d^2y)/dx^2=a^2Pe^(ax)+b^2Qe^(bx)#

So

#(d^2y)/dx^2-(a+b)dy/dx+aby# #=a^2Pe^(ax)+b^2Qe^(bx)-(a^2Pe^(ax)+abQe^(bx)+abPe^(ax)+b^2Qe^(bx)) +abPe^(ax) + abQe^(bx)=0, # as required. #square#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Kindly refer to a Proof in the Explanation.

Prerequisite : The elimination of #p and q# from the eqns. :
#px+qy+z=0, pl+qm+n=0, pu+qv+w=0# is,
#|(x,y,z),(l,m,n),(u,v,w)|=0#.
We have, #Pe^(ax)+qe^(bx)-y=0..........(1)#.
Diff.ing w.r.t. #x#, we get, #P*ae^(ax)+Q*be^(bx)-y'=0........(2)#.
Rediff.ing w.r.t. #x#, we get, #P*a^2e^(ax)+Q*b^2e^(bx)-y''=0...(3)#.
Eliminating #P and Q# from #(1),(2) and (3)#, we have,
#|(e^(ax),e^(bx),-y),(ae^(ax),be^(bx),-y'),(a^2e^(ax),b^2e^(bx),-y'')|=0#.
#:. e^(ax)e^(bx)|(1,1,-y),(a,b,-y'),(a^2,b^2,-y'')|=0#.
Since #e^(ax),e^(bx)!=0#, and applying #C_2-C_1#, we get,
#|(1,0,-y),(a,b-a,-y'),(a^2,b^2-a^2,-y'')|=0#.
#:. (b-a)|(1,0,-y),(a,1,-y'),(a^2,b+a,-y'')|=0#.
As #(b-a)ne0#, and applying #R_2-a*R_1, and R_3-a^2*R_1#,
# |(1,0,-y),(0,1,ay-y'),(0,b+a,a^2y-y'')|=0#.
Finally, expanding by #C_1#, we have,
#1*|(1,ay-y'),(b+a,a^2y-y'')|-0+0=0, i.e., #
#1(a^2y-y'')-(b+a)(ay-y')=0, or, #
# a^2y-y''-bay-a^2y+(b+a)y'=0#.
#rArr y''-(a+b)y'+aby=0# what is the same as to say that,
#(d^2y)/dx^2-(a+b)dy/dx+aby=0#.

Feel & Spread the Joy of Maths.!

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

#color(red)(y=Pe^(ax)+Qe^(bx)rArry_2-(a+b)y_1+aby=0)#
Answer for above Question is given below.

We have, #y=Pe^(ax)+Qe^(bx)# #rArry=Pe^(ax)+Q/e^(-bx)# #rArre^(-bx)y=Pe^(ax-bx)+Q# #rArre^(-bx)y-Pe^(ax-bx)=Q#, where Q is constant Diff.w.r.t.x,we gate, #e^(-bx)y_1+y(e^(-bx))(-b)-Pe^(ax-bx)(a-b)=0# Dividing both sides by, #e^(-bx)# #y_1-by-Pe^(ax)(a-b)=0rArry_1-by-(P(a-b))/e^(-ax)=0# #rArre^(-ax)y_1-be^(-ax)y-P(a-b)=0#,where P,a,b are constants. Diff.w.r.t.x,we get, #rArre^(-ax)y_2+y_1e^(-ax)(-a)-be^(-ax)y_1-bye^(-ax)(-a)=0# Dividing both sides by, #e^(-ax)# #rArry_2-ay_1-by_1-by(-a)=0# #rArry_2-(a+b)y_1+aby=0#.
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 4

To show that (d^2y)/dx^2 - (a+b)dy/dx + aby = 0 for the given function y = Pe^(ax) + Qe^(bx), we need to find the first and second derivatives of y with respect to x, and then substitute them into the differential equation.

First, find dy/dx: dy/dx = aPe^(ax) + bQe^(bx).

Next, find d^2y/dx^2: d^2y/dx^2 = a^2Pe^(ax) + b^2Qe^(bx).

Substitute these derivatives into the differential equation: d^2y/dx^2 - (a+b)dy/dx + aby = (a^2Pe^(ax) + b^2Qe^(bx)) - (a+b)(aPe^(ax) + bQe^(bx)) + ab(Pe^(ax) + Qe^(bx)) = a^2Pe^(ax) + b^2Qe^(bx) - a^2Pe^(ax) - abQe^(bx) - abPe^(ax) - b^2Qe^(bx) + abPe^(ax) + abQe^(bx) = 0.

Therefore, (d^2y)/dx^2 - (a+b)dy/dx + aby = 0 for y = Pe^(ax) + Qe^(bx).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7